Creativity where poems begin - Mackey, Mary 1945- (Marsh Hawk Press, 2022)
"Creativity: Where Poems Begin is a meditation on how the sources of creativity emerged from a vast, wordless reality and became available to me as a poet. As such, it is not only a memoir; it is an exploration of the power and process of becoming a poet. To describe creativity in words is extraordinarily difficult because the moment of creation comes from a place where language does not exist and where the categories that determine what we see, hear, taste, and feel are not immediately present. In our daily lives we tend to live on the surface, unaware of the complexity and richness of what lies below. Poetry creates itself, bubbling up from the depths until it reaches that part of our brains that transforms consciousness into words. This is a journey to that place where poems begin"--